APLIKASI AIR ALERT TRAINING UNTUK KOMPONEN BIOMOTORIK DASAR PEMAIN SEPAK BOLA EKSTRAKURIKULER SMAN 1 MONTONG GADING - Hulfian, Lalu; Wijaya Kusuma, Lalu Sapta; Subakti, Subakti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
Air Alert Training program is an training program to improve the ability of vertical jumps consisting of 6 movements. However, in sports achievements not only strength is needed, but an increase in basic biomotor components as a whole. The basic biomotor components included strength, endurance, speed, coordination, and flexibility. Because the basic biomotor component consists of anaerobic and aerobic, a training method is needed that can increase both of them together. One method that can be used is the circuit training method. The formulation of the problem in this study is 1) what basic biomotor components can be improved by modifying the Air Alert Training ?, 2) how much is the increase in the basic biomotor components due to Air Alert Training ?. The goal to be achieved in this study is to improve the basic biomotor component through modification of Air Alert Training. The research method used in this study was an experimental method because it sought a causal relationship between two variables, namely Air Alert Training on the basic motor components of extracurricular soccer players at SMAN 1 Montong Gading. This research is located at SMAN 1 Montong Gading East Lombok by taking 18 extracurricular soccer players from SMAN 1 Montong Gading. The test used is an action test for each basic biomotor component with a predetermined operational standard (SOP). The output target of this study is publication in ISSN journals and products in the form of training programs that can improve the basic biomotor components needed in preservation sports simultaneously so that it can improve the achievement of extracurricular soccer players at SMAN 1 Montong Gading. Data analysis using SPSS t test paired sample test. The results of the analysis show the value (sig.) <Î‘ (0.05), that is (0,000 <0.05), then H0 is rejected, H1 is accepted, meaning there is an increase in the basic biomotor component due to water alert training.